Regulation of body temperature and blood pressure in women: Mechanisms and implications for heat illness risk - Gabrielle E. W. Giersch; Nisha Charkoudian (Experimental Physiology)
Abstract Increasing global temperatures due to ongoing climate change phenomena have resulted in increased risk of exertional heat illness in otherwise healthy, young individuals who work or play in the heat. With increasing participation of women in athletic, military and industrial activities that involve exertion in the heat, there is a growing need to study female physiology in this context. Mechanisms controlling blood pressure and body temperature have substantial overlap in humans, largely due to autonomic mechanisms which contribute to both. Similarly, illnesses that result from excessive heat exposure can often be traced back to imbalances in one or more of these autonomic mechanisms. In recent years, there has been increased recognition of the importance of sex as a biological variable for basic and applied research in these areas. The goal of this paper is to present an update on the integrative physiology and pathophysiology of responses to heat stress in women (thermoregulation and blood pressure regulation). In this context, it is often the case that differences between sexes are presented as ‘advantages’ and ‘disadvantages’ of one sex over the other. In our opinion, this is an over‐simplification of the physiology which ignores the nuances and complexities of the integrative physiology of responses to heat exposure and exercise, and their relevance for practical outcomes.